Non-linear model of Computer Networks - Max, Gyula (Acta Agraria Kaposváriensis, 2010)
Dataflow in computer networks can not be described as a linear system. To simulate behaviours of these systems are also difficult, because these systems show non-linear features. Before implementing network equipments users want to know capabilities of their computer networks. They want to know what happens when the servers are overloaded, when temporary traffic peaks occur or when more requests arrive than the server can serve. We established a system model to study the non-linear behaviours of dataflow in the computer networks planned. This paper presents setting up a non-linear simulation model that helps us to study dataflow problems of the networks.
Keywords: non-linear system analysis; computer networks; simulation